Molecular karyotype of the white rot fungus Pleurotus ostreatus - Larraya, L.M; Perez, G; Penas, M.M; Baars, J.J.P; Mikosch, T.S.P; Pisabarro, A.G; Ramirez, L (Applied and environmental microbiology, 1999)
The white rot fungus Pleurotus ostreatus is an edible basidiomycete with increasing agricultural and biotechnological importance. Genetic manipulation and breeding of this organism are restricted because of the lack of knowledge about its genomic structure. In this study, we analyzed the genomic constitution of P. ostreatus by using pulsed-field gel electrophoresis optimized for the separation of its chromosomes. We have determined that it contains 11 pairs of chromosomes with sizes ranging from 1.4 to 4.7 Mbp. In addition to chromosome separation, the use of single-copy DNA probes allowed us to resolve the ambiguities caused by chromosome comigration. When the two nuclei present in the dikaryon were separated by protoplasting, analysis of their karyotypes revealed length polymorphisms affecting various chromosomes. This is, to our knowledge, the clearest chromosome separation available for this species.